Human Adipose Tissue-Derived Mesenchymal Stem Cells Abrogate Plasmablast Formation and Induce Regulatory B Cells Independently of T Helper Cells. (17th February 2015) - Franquesa, M.; Mensah, F. K.; Huizinga, R.; Strini, T.; Boon, L.; Lombardo, E.; DelaRosa, O.; Laman, J. D.; Grinyó, J. M.; Weimar, W.; Betjes, M. G. H.; Baan, C. C.; et al.
Abstract: Mesenchymal or stromal stem cells (MSC) interact with cells of the immune system in multiple ways. Modulation of the immune system by MSC is believed to be a therapeutic option for autoimmune disease and transplant rejection. In recent years, B cells have moved into the focus of the attention as targets for the treatment of immune disorders. Current B-cell targeting treatment is based on the indiscriminate depletion of B cells. The aim of this study was to examine whether human adipose tissue-derived MSC (ASC) interact with B cells to affect their proliferation, differentiation, and immune function. ASC supported the survival of quiescent B cells predominantly via contact-dependent mechanisms. Coculture of B cells with activated T helper cells led to proliferation and differentiation of B cells into CD19 + CD27 high CD38 high antibody-producing plasmablasts. ASC inhibited the proliferation of B cells and this effect was dependent on the presence of T cells. In contrast, ASC directly targeted B-cell differentiation, independently of T cells. In the presence of ASC, plasmablast formation was reduced and IL-10-producing CD19 + CD24 high CD38 high B cells, known as regulatory B cells, were induced. These results demonstrate that ASC affect B cell biology in vitro, suggesting that they can be a tool for the modulation of the B-cell response in immune disease. Stem Cells 2015;33:880–891